Treatment of dental polyclinic -induced gingivitis caused by secondary caries: a case report - Dinyati, Maisaroh; Mapanggara, Surijana; Adam, Andi M.; Oktawati, Sri (Journal of Case Reports in Dental Medicine, 2019)
Objective: This case report aims to present gingival therapy with gingivectomy due to secondary caries and overhanging filling.Methods: A 21-year-old male patient come to the periodontal clinic for treatment. The initial examination revealed deep probing pocket depth with sulcus bleeding at 11, 12, 21 and 22.  Teeth 34, 36, 37 were extracted. Patients was in a good health, smoker, and didn’t take any medication. The patient had scalling a week ago but the gingiva remains enlargement. Periapical radiograph showed bone in good density. Initial treatment performed by non-surgery treatment included Scalling and Root Planing (SRP) and 0.2% chlorhexidine solution twice daily for one week. Gingivectomy with conventional blade. The result of control showed reduced enlarged of gingiva and patient feel satisfied with the treatment. Control one week after surgery. After being cured clinically, composite filling applied on teeth 11 and 21.Results: Gingivitis caused by secondary caries, because of bacterial invasion of caries to the gingival mucosa. Gingivitis therapy performed by gingivectomy, the removal of amount of the hyperplated gingival mucosa. Conventional gingivectomy is an option of gingival enlargement therapy.Conclusion: The aim of gingival therapy is to eliminate inflammatory process and prevent the progression of gingival disease. Gingival disease including gingival enlargement or gingivitis. Gingivitis can be caused by various factors such as secondary caries and overhanging filling. Keywords:  Gingival enlargement, Gingivectomy, Seconder caries.